Gliomatosis Peritonei: Report of Two Cases and Literature Review - Huang, MD, PhD, Jialing; Atienza, MD, Robbie; Pulinthanathu, MD, Rajiv (North American Journal of Medicine and Science, 2017)
Gliomatosis peritonei (GP) is a rare condition characterized by intraabdominal (peritoneal, nodal and omental) implants of glial tissue. GP is believed to be commonly associated with immature ovarian teratoma and possesses favorable prognosis. However, the origin of GP is controversial and its clinical outcomes vary. Here we reported 2 cases of GP arising in mature and immature ovarian teratoma, respectively. Recent literature is also reviewed. [N A J Med Sci. 2017;10(1):36-39. DOI: 10.7156/najms.2017.1001036]